The Security System as a Key Element of the Production System - Jarosław Napiórkowski; Jerzy Stanik; Henryk Popiel (Communications of International Proceedings, 2020)
The article presents the concept (generalized model) of the safety system for the purposes of maintaining or measuring the required level of safety of the production system. The basic elements of the model were highlighted and characterized from the point of view of controlling risk levels in functional and information security. The proposed concept of measuring the quality and state of safety, takes into account the impact of such factors as: the level of risk of internal and external threats to the basic elements of the production system, changes in the operating conditions of both production processes and computer systems supporting these processes, the vulnerability of technical and organizational security mechanisms.
Keywords: Security; Production System; Safety Management System.